A new process for the utilization of Antarctic krill - Ellingsen, Trond E.; Mohr, Viggo (Process Biochemistry, 1979)
Keywords: NARE 1976/77; Sørishavet; biokjemi; krill; lyskreps; marinbiologi; plankton

Antarktisk krill : deteksjon - fangst - anvendelse; teknisk / økonomisk analyse - Fiskerstrand, Rolf (Universitetet i Trondheim Norges tekniske høgskole, Institutt for skipsprosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; krill; zooplankton; økonomi

Norsk fangst av antarktisk krill : teknisk/økonomisk analyse - Fiskerstrand, Rolf (Norges fiskerihøgskole, Universitetet i Trondheim, Norges tekniske høgskole, Institutt for marin prosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; historie; hvalfangst; krill; pelagisk; zooplankton; økonomi

Fluoride in Antarctic Krill (Euphausia superba) and Atlantic Krill (Meganyctiphanes norvegica) - Soevik, Torleif; Braekkan, Olaf R. (Journal of the Fisheries Research Board of Canada, 1979)
Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Key words: krill, red feed, deep sea prawn, fluoride.
Keywords: Sørishavet; biokjemi; forurensning; krill; marin biologi; miljøgifter; plankton

Innstilling fra utvalg for utredning av mulighetene for fangst og anvendelser av krillressursene i Antarktis - Heen, Eirik (s.n., 1976)
Keywords: Sørishavet; ekspedisjoner; fangst; krill; zooplankton